An improved nuclei isolation protocol from leaf tissue for single-cell transcriptomics - Gabriela Madrid; Gabriel Angelo Saraiva Raimundo; Fabian Andres Reyes; Edgard Augusto de Toledo Picoli; Marcio F. R. Resende Jr.; Kelly M. Balmant (PLoS ONE, 2025)
The study of plant biology has traditionally focused on investigations conducted at the tissue, organ, or whole plant level. However, single-cell transcriptomics has recently emerged as an important tool for plant biology, enabling researchers to uncover the expression profiles of individual cell types within a tissue. The application of this tool has revealed new insights into cell-to-cell gene expression heterogeneity and has opened new avenues for research in plant biology. A critical step in the successful application of single-cell and single-nuclei RNA-seq (scRNA-seq and snRNA-seq) is the isolation of individual cells or nuclei, respectively, from tissue to recover their transcriptional profile. A critical step during nuclei isolation for snRNA-seq studies is Fluorescent-Activated Cell Sorting (FACS). During this step, nuclei stained with DAPI (4′,6-diamidino-2-phenylindole) can be sorted and separated from cell debris and organelles. Leaf tissue presents a unique challenge due to its high content of chloroplasts, which can interfere with obtaining high-quality results. Because DAPI can also bind to the plastid genome, these organelles will be sorted as nuclei. Thus, in tissues with a high content of chloroplasts, we have a high contamination of these organelles and an overestimation of the number of nuclei. In this study, we introduce a straightforward alternative method for isolating nuclei from Zea mays leaves with reduced chloroplast contamination. By effectively removing chloroplasts during the FACS step of our protocol, using the autofluorescence from the chloroplasts, we achieved improved alignment of reads to the genome and transcriptome. Our enhanced protocol offers a valuable solution for applying snRNA-seq in tissues with a high content of chloroplasts.